Trans-cortical vessels in the mouse temporal bulla bone are a means to recruit myeloid cells in chronic otitis media and limit peripheral leukogram changes - Azar, Ali; Bhutta, Mahmood F.; Del-Pozo, Jorge; Milne, Elspeth; Cheeseman, Michael (Frontiers in Genetics, 2022)
Chronic otitis media, inflammation of the middle ear, is a sequel to acute otitis media in ~8% of children. Chronic otitis media with effusion is the most common cause of childhood deafness and is characterised by effusion of white blood cells into the auditory bulla cavity. Skull flat bones have trans-cortical vessels which are responsible for the majority of blood flow in and out of the bone. In experimental models of stroke and aseptic meningitis there is preferential recruitment of myeloid cells (neutrophils and monocytes) from the marrow in skull flat bones. We report trans-cortical vessels in the mouse temporal bone connect to the bulla mucosal vasculature and potentially represent a means to recruit myeloid cells directly into the inflamed bulla. The mutant mouse strains Junbo (MecomJbo/+) and Jeff (Fbxo11Jf/+) develop chronic otitis spontaneously; MecomJbo/+ mice have highly cellular neutrophil (90%) rich bulla exudates whereas Fbxo11Jf/+ mice have low cellularity serous effusions (5% neutrophils) indicating differing demand for neutrophil recruitment. However we found peripheral leukograms of MecomJbo/+ and Fbxo11Jf/+ mice are similar to their respective wild-type littermate controls with healthy bullae and infer preferential mobilization of myeloid cells from temporal bulla bone marrow may mitigate the need for a systemic inflammatory reaction. The cytokines, chemokines and haematopoietic factors found in the inflamed bulla represent candidate signalling molecules for myeloid cell mobilization from temporal bone marrow. The density of white blood cells in the bulla cavity is positively correlated with extent of mucosal thickening in MecomJbo/+, Fbxo11Jf/+ and EdaTa mice and is accompanied by changes in epithelial populations and bone remodelling. In MecomJbo/+ mice there was a positive correlation between bulla cavity WBC numbers and total bacterial load. The degree of inflammation varies between contralateral bullae and between mutant mice of different ages suggesting inflammation may wax and wane and may be re-initiated by a new wave of bacterial infection. Clearance of white blood cells and inflammatory stimuli from the bulla cavity is impaired and this may create a pro-inflammatory feedback loop which further exacerbates otitis media and delays its resolution.